2011
DOI: 10.1253/circj.cj-10-1106
|View full text |Cite
|
Sign up to set email alerts
|

Less Frequent Opening of the Aortic Valve and a Continuous Flow Pump Are Risk Factors for Postoperative Onset of Aortic Insufficiency in Patients With a Left Ventricular Assist Device

Abstract: Background: Postoperative development of aortic insufficiency (AI) after implantation of left ventricular assist devices (LVADs) has recently been recognized, but the devices in the previous reports have been limited to the HeartMate I or II. The purposes of this study were to determine whether AI develops with other types of LVADs and to elucidate the factors associated with the development of AI. Methods and Results:Thirty-seven patients receiving LVADs without evident abnormalities in native aortic valves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 27 publications
2
69
0
4
Order By: Relevance
“…47,48 About 80% of patients without preoperative valve regurgitation showed rapid development of mild to moderate aortic regurgitation following their LVAD implantation. 49 This "de novo" aortic regurgitation induced by the LVAD is considered to have deleterious effects on pump efficiency and systemic output. In fact, this creates a circulatory loop of flow to the ventricle instead of the systemic circulation, diminishing the efficiency of support and the ventricular unloading.…”
Section: Aortic Regurgitationmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 About 80% of patients without preoperative valve regurgitation showed rapid development of mild to moderate aortic regurgitation following their LVAD implantation. 49 This "de novo" aortic regurgitation induced by the LVAD is considered to have deleterious effects on pump efficiency and systemic output. In fact, this creates a circulatory loop of flow to the ventricle instead of the systemic circulation, diminishing the efficiency of support and the ventricular unloading.…”
Section: Aortic Regurgitationmentioning
confidence: 99%
“…Remarkably, in a small number of patients, the aortic regurgitation manifests only in the systolic phase of the cardiac cycle and probably would disappear at the opening of the aortic valve. 49,51 The mechanism involved in this LVAD-related systolic aortic regurgitation is still unknown, but may involve a different mechanism associated with dynamic modification of the aortic annulus or valve as a result of turbulence in the ascending aorta. However, when aortic regurgitation becomes more severe, valve repair may eventually be inevitable.…”
Section: Aortic Regurgitationmentioning
confidence: 99%
“…Regurgitation through the aortic valve (AV) diminishes systemic perfusion, elevates left heart filling pressures and increases LVAD flow (1,2). This derangement is compounded by the progression of even minor aortic insufficiency with time on device support (2)(3)(4)(5)(6)(7)(8). Furthermore, existing mechanical aortic prostheses convey an increased risk for stroke from thromboembolism (2).…”
Section: Introductionmentioning
confidence: 99%
“…17) We also showed that AI was more frequently observed in patients with CF LVAD as compared with PF pump in 2011 ( Figure 1C). 18) Since then, a number of single-center studies have documented a wide-ranging prevalence of AI during LVAD treatment. 15,[19][20][21] The development of AI during LVAD treatment is considered to be a multifactorial phenomenon and a result of altered AV and aortic root biomechanics due to chronic and continuous ventricular unloading.…”
mentioning
confidence: 99%
“…34) Native AV can be replaced with a bioprosthetic valve, but newly placed biologic valves are still at risk for the development of postoperative AI. 18) Park, et al first reported a simple technique of concomitant AV repair at the time of LVAD implantation (Park's stitch), 35,36) but the repair also carries a risk for recurrence of AI. Patch closure of the outflow tract is another strategy.…”
mentioning
confidence: 99%